APPLICATION OF RECTAL EXPLORATION TECHNIQUES FOR PREGNANCY DIAGNOSIS IN GOATS - Saifudin, Ali; Aslimah, Siti; D. Putra, Teguh; Hadisutanto, Bambang (Fakultas Peternakan, Universitas Padjadjaran, 2024)
This study aims to explore the potential of applying rectal exploration (ER) techniques to goats for practical purposes. The principle of pregnancy detection in this technique is based on palpable gestational changes in the goat's reproductive tract in terms of location, consistency, and size. This study used 6 female goats aged 2-3 years with normal reproductive cycles and had given birth and one fertile male goat at the age of 2-3 years. Mating was carried out naturally. Previously, female goats had been in estrus synchronization with a double injection of prostaglandin 1.5 ml/head each intramuscularly with an interval of 11 days. Pregnancy tests were carried out at 30, 40, 50, and 60 days after mating using Real-Time B-Mode Ultrasonography (USG) and ER techniques. In this study, ultrasound was used as the gold standard because this method is more accurate and reliable for the diagnosis of pregnancy in small ruminants. The diagnostics observed in this study were the sensitivity and specificity of the ER technique for diagnosing pregnancy in goats compared to the gold standard. The results showed that four goats that were negatively pregnant with the ER technique also showed that they were not pregnant on ultrasound on all days of the examination stage, and two goats that were positive for pregnancy with ultrasound showed positive pregnancy with the ER technique on examination 50 and 60 days after mating. Based on the results of this study, it can be concluded that the ER technique can be used for an alternative pregnancy diagnosis in goats that is practical in the field.